Exploring eco-anxiety among women amid climate-induced heat: a comprehensive review - K. G, Gayathri; P, Vijayalakshmi; S, Krishnan; S, Rekha; P. K, Latha; Venugopal, Vidhya (Frontiers in Psychology, 2025)
Eco-anxiety, the chronic fear of environmental doom, has become more frequent as climate change accelerates, particularly among disadvantaged population. This comprehensive review explores the relationship between eco-anxiety and gender differences, with a particular emphasis on women who experience stress and summarises the existing literature on the psychological and emotional responses to heat-related climate stressors. The current review critically examined a total of 21 articles and synthesised the scholarly literature on eco-anxiety, then it was reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA-ScR). Women often face socioeconomic and physiological challenges, leading them to be more vulnerable to the effects of climate change, such as extreme heat events. This review was mainly focussed on the climate induced pathways to psychological consequences and gender differences with respect to eco-anxiety which strives to reveal targeted support systems and promote more inclusive climate resilience planning by comprehending the gender-specific dimensions of eco-anxiety. We observed that most of the evidence were from Western countries, hence global research is essential. According to our review, further study is needed to define eco-anxiety with respect to climate induced heat.